Pelatihan Pemanfaatan Alat Peraga dalam Model PjBL Sebagai Optimalisasi Kurikulum Merdeka di SMP - Harijanto, Alex; Nuraini, Lailatul; Bektiarso, Singgih; Subiki, Subiki; Maryani, Maryani; Prabandari, Audri Mely; Chandhani, Erika Divian; Pratiwi, Anisa Septi (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Learning Props are teaching aids designed to accompany project-based learning activities. This community service is motivated by the problems faced by educators when implementing project-based learning models. Therefore an innovation is needed for these problems. SMP PGRI 1 Tempurejo is a target school in Jember district that is still less educated about the use of teaching aids in project-based learning models to support the implementation of an independent learning curriculum. This service activity is carried out in three stages, namely the preparation stage, the implementation stage, and the evaluation and reporting stage. The activities carried out in this community service are conducting training on the use of teaching aids media in project-based learning models to support the implementation of an independent learning curriculum for teachers and students at SMP PGRI 1 Tempurejo Jember. PhET media is an interactive simulation media that is given to students to facilitate practicum that cannot be done directly or real but uses a virtual laboratory that is effective in learning. In the training activities, teachers and students responded quite well, this was indicated by the response of teachers and students who stated that they knew about PhET media in the project-based learning model after conducting training. Based on the results, it can be concluded that the participants who took part in the training increased their insight, knowledge and skills about the use of teaching aids in the project-based learning model as a support for the implementation of an independent learning curriculum.